A Novel Technique for Thoracic Endovascular Graft Explantation. Issue 2 (March 2023) - Frydman, Asher A.; Paquet, Maude; Xing, Chuce; Valdis, Matthew; Power, Adam; Chu, Michael W. A.
Thoracic endovascular aortic repair (TEVAR) explantation remains a challenge due to endovascular graft ingrowth into the aortic wall with time. Surgical access into the aortic arch can be difficult either via sternotomy or thoracotomy, and proximal barbs become engaged firmly into the aortic wall. Explantation often requires extensive thoracic aortic resection, sometimes from the distal aortic arch to the abdominal aorta, followed by reconstruction, risking injury to surrounding neurovascular structures and even death. In cases of blunt thoracic aortic injury, the original injury is often healed, and failed TEVAR could theoretically be removed when thrombotic complications occur. We present a novel technique to facilitate TEVAR recapture with limited distal thoracic aorta replacement. Visual abstract